Strengthening the Indonesian Migrant Worker Protection System through a Strategic Approach to Migration Policy - Wakhidatul Mubarokah; Rodiyah Rodiyah (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the regulation and implementation of the Indonesian Migrant Worker (PMI) protection system and evaluate its effectiveness and fairness in addressing vulnerabilities across the migration cycle. This research employs a qualitative socio-legal approach through in-depth interviews with the Director of SARI Solo and former migrant workers in Bojasari Village, supported by analysis of relevant laws and policy documents. The findings indicate that although Law Number 18 of 2017 provides comprehensive protection covering pre-placement, placement, and post-placement stages, its implementation remains constrained by weak preventive protection, limited access to complaint mechanisms, and inadequate social and economic reintegration programs. The study also finds that community-based approaches through the empowerment of migrant workers and their families significantly strengthen legal protection effectiveness by improving legal awareness, social resilience, and access to social protection. Therefore, strengthening the migrant worker protection system requires the integration of national legal frameworks with community-based empowerment mechanisms to ensure more effective, equitable, and sustainable protection.